Tackling an intractable problem: Can greater taxon sampling help resolve relationships within the Stenopelmatoidea (Orthoptera: Ensifera)? - Vandergast, Amy G.; Weissman, David B.; Wood, Dustin A.; Rentz, David C. F.; Bazelet, Corinna S.; Ueshima, Norihiro (Zootaxa, 2017)
The relationships among and within the families that comprise the orthopteran superfamily Stenopelmatoidea (suborder Ensifera) remain poorly understood. We developed a phylogenetic hypothesis based on Bayesian analysis of two nuclear ribosomal and one mitochondrial gene for 118 individuals (84 de novo and 34 from GenBank). These included Gryllacrididae from North, Central, and South America, South Africa and Madagascar, Australia and Papua New Guinea; Stenopelmatidae from North and Central America and South Africa; Anostostomatidae from North and Central America, Papua New Guinea, New Zealand, Australia, and South Africa; members of the Australian endemic Cooloola (three species); and a representative of Lezina from the Middle East. We also included representatives of all other major ensiferan families: Prophalangopsidae, Rhaphidophoridae, Schizodactylidae, Tettigoniidae, Gryllidae, Gryllotalpidae and Myrmecophilidae and representatives of the suborder Caelifera as outgroups. Bayesian analyses of concatenated sequence data supported a clade of Stenopelmatoidea inclusive of all analyzed members of Gryllacrididae, Stenopelmatidae, Anostostomatidae, Lezina and Cooloola. We found Gryllacrididae worldwide to be monophyletic, while we did not recover a monophyletic Stenopelmatidae nor Anostostomatidae. Australian Cooloola clustered in a clade composed of Australian, New Zealand, and some (but not all) North American Anostostomatidae. Lezina was included in a clade of New World Anostostomatidae. Finally, we compiled and compared karyotypes and sound production characteristics for each supported group. Chromosome number, centromere position, drumming, and stridulation differed among some groups, but also show variation within groups. This preliminary trait information may contribute toward future studies of trait evolution. Despite greater taxon sampling within Stenopelmatoidea than previous efforts, some relationships among the families examined continue to remain elusive.